Effects of fatigue on leg kinetics during all-out 600m running - Kadono, H.; Ae, M.; Suzuki, Y.; Shibayama, K. (International Journal of Sport & Health Science, 2013)
The purpose of this study was to investigate the effects of fatigue on ground reaction forces and leg kinetics during all-out 600m running. Eight male middle-distance runners were asked to perform two kinds of running, i.e. an all-out 600m run and a non-fatigued 80m run with the same velocity as at the 550m mark of the 600m run. Their running motion was videotaped and the ground reaction forces were measured at the 150m and 550m marks of the 600m run and at the 50m mark of the 80m run. The step length, ground reaction forces, ankle plantar flexion torque, and knee extension torque of the support leg decreased due to fatigue. The hip joint torque of the recovery leg decreased due to the difference in running speed rather than fatigue. From these results, we suggest that in the final stage of 800m race, a runner should not try to extend the step length by thrusting against the ground with the support leg but should maintain the step time as much as possible by moving the recovery leg quickly.